1996
DOI: 10.1055/s-2007-979859
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Estrogens, Progesterone and their Antagonists on the Collagen Content in the Pregnant Rat Uterus

Abstract: The influence of progesterone, estrogens and their antagonists: mifepristone and tamoxifen on connective tissue metabolism in pregnant rat uterus near term was evaluated. Total collagen and its soluble fraction as well as water concentration was measured in a population of 65 pregnant rats; treated with progesterone (n = 10), mifepristone (n = 13), estradiol (n = 17) and tamoxifen (n = 12). The results suggest the important influence of sex steroids on the uterine connective tissue metabolism during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The same phenomenon can be confirmed by the immunohistochemical results, which reveal the reduced intensity of immunostaining in all layers of the uterus as the end of the gestational period approached. Considering the fact that rat uterine tissue has a low connective tissue content (less than 6%) and the hormonal changes towards the end of pregnancy furtherly reduce its amount (Bieńkiewicz et al, 1996), it can be stated that the connective tissue mass is marginal as compared with that of smooth muscles. Since no data is available about the Kiss1r expression in any connective tissue (and its probability is very low), we suppose that the immunostaining revealed the Kiss1r expression in the smooth muscle of the non-pregnant and pregnant rat uteri.…”
Section: Discussionmentioning
confidence: 99%
“…The same phenomenon can be confirmed by the immunohistochemical results, which reveal the reduced intensity of immunostaining in all layers of the uterus as the end of the gestational period approached. Considering the fact that rat uterine tissue has a low connective tissue content (less than 6%) and the hormonal changes towards the end of pregnancy furtherly reduce its amount (Bieńkiewicz et al, 1996), it can be stated that the connective tissue mass is marginal as compared with that of smooth muscles. Since no data is available about the Kiss1r expression in any connective tissue (and its probability is very low), we suppose that the immunostaining revealed the Kiss1r expression in the smooth muscle of the non-pregnant and pregnant rat uteri.…”
Section: Discussionmentioning
confidence: 99%
“…In a complex research project we are currently investigating various influences affecting the physiology of the uterine cervix. Among these influences, the effects of hormones on the supply of blood, oxygen and water in the cervix is an important focus [4]. We recently demonstrated that FD-NIRS technology is highly sensitive and accurate in detecting changes in cervical physiology [3,10].…”
Section: Discussionmentioning
confidence: 99%
“…We recently demonstrated that prostaglandininduced cervical ripening results in a significant change in optical properties (i.e., the absorption and scattering of light), a significant decrease in total hemoglobin (tHb), oxyhemoglobin (O 2 Hb), deoxyhemoglobin (HHb), and a highly significant increase in water content (H 2 O) [3]. So far, the influence of sex hormones on the optical properties of the human uterine cervix has not been investigated, but it is likely to be important in the process of cervical ripening [4].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, regarding the results of immunohistochemistry, it should be clarified that the methods used in this study were not suitable for quantitative measurements. However, considering the fact that rat uterus has a low connective tissue content and its amount is further reduced due to hormonal changes towards the end of pregnancy 84 , it can be stated that the amount of connective tissue is marginal as compared with that of smooth muscle. Generally, we can state that immunostaining revealed the adipokine receptor expressions in the smooth muscle of the non-pregnant and pregnant rat uteri.…”
Section: Discussionmentioning
confidence: 99%